Analisis Tugas dan Fungsi BAPPEDA terhadap Pelaksanaan Koordinasi Rencana Pembangunan Jangka Menengah Daerah - Setiadi Setiadi; Irwan Nasution; Armansyah Matondang (PERSPEKTIF, 2018)
The 2012-2017 Regional Medium Term Development Plan (RPJMD) prepared by the BAPPEDA of Bener Meriah District has its own goals, strategies and policy directions so that the development goals to achieve the vision and mission of Bener Meriah District can be realized, but there are still obstacles to implementation. so that the RPJMD targets and targets are not implemented optimally. Therefore, the authors are interested in examining the Task and Function of the Bappeda on the Implementation of the 2017 Bener Meriah District RPJMD Coordination and the Factors that Inhibit the Implementation of the Coordination of 2017 Bener Meriah District Medium Term Development Plans (RPJMD) that  have  been  implemented.  The research method used with this type of qualitative research approach is descriptive as a method of data analysis. Data collection techniques used by the authors in this study are interview techniques, documentation and observation questionnaires. Based on the analysis, the implementation of regional development coordination carried out by BAPPEDA of Bener Meriah District in accordance with its main tasks and functions through inter-sector coordination meetings and SKPD, Forum Group Discussion (FGD), as well as through village, subdistrict, district, provincial and national musrenbang there are still obstacles. Constraints faced were frequent delays in the collection of SKPK work plans and other supporting data which resulted in BAPPEDA in coordinating difficulties in implementing development planning.